The Combination Time and Temperature to Aloe Vera Skin Tea as Functional Drink - Narsih Narsih; Agato Agato (Faculty of Animal Science Universitas Brawijaya, 2017)
This study gets started by making the dry tea from aloe vera skin. The making of aloe vera skin tea was used the cabinet drying. The stem of aloe vera its green coloring was spread evenly on the surface was stacked on the plastic basket that lined with the paper. The steps were carried out to sorting, cleaning, weighing, and peeling off the stem continued by separating the gel and skin of the aloe vera. The aloe vera skin was dried on the cabinet drying at 60Â°C for 4 hours, then brewed using the water at 70, 80, and 90Â°C for 1 and 3 minutes. The best result from each parameter such as tannin, phenol, alkaloid, and antioxidant activity would be continued by GCMS test to identify the volatile compounds and the organic acid as the compiler of the brewed tea by using HPLC test.